Pacing strategy of the finishers of the world marathon majors series - Kais, Ülari (Array, 2019)
The purpose of the study was to describe pacing patterns of the finishers of the World Marathon Majors series and the effect of sex and age on the pacing pattern. The finishers of the World Marathon Majors series, a total of 69 814 male runners and 46 856 female runners with finishing time ≤ 6 hours were included in the analysis. Difference in pacing (dev%) was calculated as a difference between the first and second half of the marathon and expressed as a percentage of time. Analysis of variance (ANOVA) was used to evaluate the differences within and between the marathon time groups. The differences between the first and second half of the marathon by sex and age group were analysed using linear regression. The average difference between the first and second half of the marathon was 3.44±2.67% for male and 2.81±2.10% for female runners. Male runners with finishing times of 3:00 (h:min) and females with 4:00 (h:min) or slower had the significantly faster first half of the marathon compared to the evenly paced marathon (p=.038 and p=.001, respectively). Regression analysis revealed that female runners had 0.26% smaller difference between the first and second half of the race compared to male runners (R2=0.256; p<.001) when controlled for age and time group. Also, veterans (40 years and older) paced more evenly compared to non-veterans (R2=0.256; p<.001). In conclusion, irrespective of sex and age, faster finishers maintain a more constant velocity than the slower ones. In addition, women and veterans present more even pacing strategy compared to men and non-veterans, respectively.